PEMBAHARUAN KOMITE SEKOLAH DALAM PEMBERDAYAAN ORGANISASI - Merzon Merzon (UNIVERSITAS BENGKULU, 2015)
The objective of this research is to describe the reconditional school committee in empowerment of organization In elementary school 04 Arga makmur of north Bengkulu district.The method in this research is descriptive qualitative. There are three data collecting techniques used in the research, namely: interview, documentation, and observation. While techniques ofanalyzing data applied is interactive analysis. The result of this research shows: there are innovation that is done by school committee in human resource, management resource, leadership resource in elementary school 04 arga makmur of north Bengkulu district. There is no innovation in monetary and facility resource that done by school committee in elementary school 04 arga makmur of north Bengkulu district.Key words: school committee, organization.